AB0392 Safety and effectiveness of CT-P13 in patients with rheumatoid arthritis: results from 24 months nationwide registry in korea. (15th June 2017) - Park, SH; Nah, SS; Chang, SH; Kim, KJ; Park, KS; Lee, SS; Kwon, SR; Lee, SI; Suh, CH; Kim, SH; Son, CN; Min, JK; et al.
Abstract : Background: CT-P13 is approved in both European Union and United States, and licensed for use in 79 countries around the world as a biosimilar to innovator infliximab (INX). The independent registries of CT-P13 have been conducted in a number of European countries and Korea [1]. Objectives: To evaluate safety and effectiveness of CT-P13 when administered in a real-life setting in active RA patients. Methods: This study collected data of patients who were treated with CT-P13 from 2013 December to 2016 June. Efficacy was assessed at baseline and every 6 months thereafter using DAS28 (ESR) and/or DAS28 (CRP) and collection of adverse events (AEs) was performed. Immunogenicity was assessed at baseline, Week 30 and every year during CT-P13 treatment period. Results: Total 125 patients were enrolled; 104 patients started treatment with CT-P13 (Naïve group) and 21 patients (8 from INX, 13 from other anti-TNFs) switched treatment to CT-P13 (Switching group). The mean (SD) duration since RA diagnosis was 6.5 (±6.85) years for all patients. Of all patients treated with CT-P13, only 4.8% (6/125) of patients changed to other anti-TNFs. Two of six patients changed treatment within 8 month after starting CT-P13. The proportion of patients achieving clinical remission by DAS28 (ESR/CRP) increased gradually (Figure 1 ). DAS28 (ESR/CRP) value decreased from baseline at 6 months and it maintained thereafter (Table 1 ). Switching group also showed similar results that remission rate by DAS28 (CRP) was 42.9% (3/7) and mean actual value was 2.85 at 12 months. For Naïve group, 50% (52/104) of patients had at least one positive anti-drug antibody result and it is consistent to other published study [2]. Overall safety summarized as the percentage of patients with at least one treatment emergent AE (TEAE) was similar or lower after switching to CT-P13 (Table 2 ). No cases of active tuberculosis were reported. Conclusions: The overall safety profile revealed that CT-P13 is well-tolerated in patients with RA and remission rate for 24 months also showed that CT-P13 is efficacious under real world practice. References: Glintborg et al. ACR 2016. Krintel et al. Rheumatology 2013. Disclosure of Interest: None declared